User Satisfaction and the Impact of User Characteristics on A Library Automation System SLiMS 9 Bulian - Saputra, Andi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
SLiMS 9 Bulian is a widely used library automation system in Indonesian libraries. This study aimed to assess user satisfaction and examine the influence of user characteristics—such as gender, age, and education level—on the performance of the SLiMS 9 Bulian. A quantitative approach was employed, using the PIECES (Performance, Information, Economy, Control, Efficiency, and Service) framework to measure user satisfaction. Data were collected through online surveys over two months (November to December 2023), with a sample of 96 librarians and library staff from 15 university libraries across West Sumatra (45%), Riau (30%), and Bengkulu (24%). After validity and reliability testing, 61 valid responses were obtained. The study found an overall satisfaction score of 4.34 out of 5. Hypothesis testing showed no significant impact of gender, age, or education level on user satisfaction (p > 0.05). The study concluded that user satisfaction with SLiMS 9 Bulian was high and that librarians are a more suitable respondent group for evaluating information systems using the PIECES framework than students. This study provides important insights into user satisfaction with SLiMS 9 Bulian, offering practical recommendations for improving library automation systems. It also highlights the value of selecting appropriate respondent groups in evaluating system performance, contributing to better-informed decisions in the development and optimization of library technologies.